(untitled) (Physical Sciences and Technology, 2020)
This paper presents the results of a study of changes in structural characteristics, such as the degree of crystallinity, dislocation density, and deformation of the crystal lattice in ZrO2 ceramics as a result of irradiation with heavy Kr15+ ions with an energy of 147 MeV. The choice of the type of irradiation ions is due to the possibility of simulating the processes of defect formation comparable to the irradiation of radiation-resistant materials by fragments of uranium fission. The radiation doses ranged from 5х1013 to 1х1016 ion/cm2. The dependences of the change in the crystallographic parameters on the radiation dose were established. At the same time, the maximum decrease for an irradiation dose of 1x1016 ion/cm2 was no more than 10 %, which in turn indicates a high radiation resistance to the accumulation of defects during large-dose irradiation. It was determined that the greatest change in the degree of crystallinity is observed above a dose of 1х1015 ion/cm2. The data obtained indicate a high degree of resistance of these ceramics to radiation damage.